Impact of a nutrition education programme on the nutritional status of children aged 3 to 5 years and the nutritional practices and knowledge of their caregivers in rural Limpopo province, South Africa - Mushaphi, Lindelani Fhumudzani (University of the Free State, 2011)
Globally, the prevalence of acute malnutrition and micronutrient deficiency is high in young children, especially in developing countries. This study was undertaken to determine the impact of a nutrition education intervention programme (NEIP) on the nutritional knowledge and practices of caregivers, as well as the nutritional status of children between the ages of three to five years in the Mutale Municipality in Vhembe district, Limpopo Province. A pre-test–post-test control group design was chosen using eight villages (four villages in the experimental group (E); four villages in the control group (C). At baseline, the study population was 125 caregivers and 129 children aged three to five years (E = 66; C = 63 children). After intervention, 86 caregivers and 89 children (E = 40; C = 49 children) were found. Only participants who participated at baseline and postintervention were included for comparison. A valid structured interview schedule was used to determine nutritional practices and knowledge. The nutrient intake was determined by two 24-hour recalls. Weight and height (to determine weight/height status) and blood samples (vitamin A and iron status) were taken using standard techniques. The NEIP was developed by the researcher using South African Food-based Dietary Guidelines (SAFBDGs) and South African Paediatric Food-based Dietary Guidelines (SAPFBDGs) as basis. The NEIP was implemented on the experimental group on two occasions, namely every week during the first three months and then during the last three to four months in a period of 12 months. Data were analysed using Statistical Analysis Software (SAS®) version 9.2 and expressed using median, minimum and maximum values to describe continuous data. Frequencies and percentage were used to describe categorical data and 95% confidence intervals were used for median and percentage differences to determine the impact of the intervention programme. The 24-hour recall data were analysed using Food Finder III version 1.1.3. The study revealed that the socio-demographic information and anthropometric nutritional status of the children did not change after intervention in both groups. Furthermore, at baseline, nearly one third of the children in both groups had marginal vitamin A status. However, after intervention, all children in both groups had adequate to normal vitamin A status, which could be due to the vitamin A supplementation and food fortification programme of the SA Government. The iron indicators were within adequate levels at pre- and post-intervention in both groups. The impact of NEIP was observed in some of the nutritional practices, since the majority of caregivers usually included starchy foods, protein-rich foods and vegetables in the child’s plate daily at baseline in both groups. However, the number of children who were given more than three meals per day showed a tendency towards an increase in the experimental group. The intake of milk and yoghurt improved significantly in the experimental group. The majority of children were eating indigenous foods. However, the intake of black jack, spider flower, wild jute plant, baobab fruit, paw-paw, mopani worms and termites improved significantly in the experimental group. The median carbohydrate and protein intake was adequate when compared to EAR/RDA in both groups at pre- and post-intervention. The median energy, carbohydrate and plant protein intake had increased significantly in the control group. The intake of iron and folate had increased significantly in both groups, while zinc intake increased significantly in the control group. After the intervention, the intake of tshimbundwa (traditional bread made with maize) also increased significantly in the control group. Furthermore, the intake of stinging nettle, meldar, wild peach, pineapple, dovhi, tshigume and thophi had improved significantly in both groups. The nutrition knowledge score was good at baseline, as the majority of caregivers in both groups were aware that children should be given a variety of foods, indigenous foods, starchy foods, protein-rich foods, vegetables and fruit. However, in the experimental group the percentage of caregivers who knew that children should be given full-cream milk and fat increased significantly at post-intervention. On other hand, the percentage of caregivers who knew tshimbundwa increased significantly in the control group. The majority of caregivers were including most of the food items on the child’s plate (starchy, protein-rich foods, vegetables and indigenous) at baseline, which left little room for improvement. However, the impact of NEIP was observed in some nutritional practices. On the other hand, minimal impact of the NEIP on nutrition knowledge was observed, since most of the caregivers had good nutritional knowledge at baseline. It is recommended that the NEIP developed in this study be adapted for the Department of Health (Nutrition Section) so that healthcare workers can present it in different communities using different media so as to increase coverage.
Keywords: Thesis (Ph.D. (Nutrition and Dietetics))--University of the Free State, 2011; Nutrition -- Evaluation -- South Africa -- Limpopo; Malnutrition in children -- South Africa -- Limpopo; Children -- Nutrition -- South Africa -- Limpopo; Indigenous foods; Nutrition education programme; Micronutrients status; Nutritional knowledge; Nutritional Practices; Nutritional status